Transcriptional and Functional Programming of Decidual Innate Lymphoid Cells - Vazquez, Jessica; Chasman, Deborah A.; Lopez, Gladys E.; Tyler, Chanel T.; Ong, Irene M.; Stanic, Aleksandar K. (Frontiers in Immunology, 2020)
A successful pregnancy requires many physiological adaptations from the mother, including the establishment of tolerance towards the semiallogeneic fetus. Innate lymphoid cells (ILCs) have arisen as important players in immune regulation and tissue homeostasis at mucosal and barrier surfaces. Dimensionality reduction and transcriptomic analysis revealed the presence of two novel CD56Bright decidual ILCs that express low T-bet and divergent Eomes levels. These cells persist across pregnancy as we found that their transcriptome correlates highly with recently identified first trimester decidual dNKs. Functional analysis revealed polyfunctional profiles that depend on the nature of the stimulus, with a preference for IFNg and VEGF production. Overall, our data reveals persistence and polyfunctional progestational functional capacity of unique decidual innate lymphocytes across pregnancy.